The Black Sea - the Geopolitical Springboard of the Region - Zakaradze, Ekaterina; Muradishvili, Khatuna (European Scientific Journal, ESJ, 2023)
Security and stability are essential for stable development, successful integration into global political and economic systems, and sustainable economic growth in the Black Sea region and Black Sea countries, including Georgia. During the Cold War, the Black Sea was "divided" into the Republic of Turkey (as a member of NATO) on one hand, and the countries of the former Soviet Union on the other. After the end of the Cold War, the strategic balance in the Black Sea region has undoubtedly changed - the role and geopolitical-economic importance of the Black Sea has noticeably increased. The Black Sea coastal states, including Georgia and Ukraine, have been given a new geopolitical role, new opportunities, and new challenges.